2012
DOI: 10.1177/1049909112461842
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cancer and Noncancer Patients Who Receive Palliative Care Consultation Services

Abstract: This study aimed to compare multiaspect characteristics in cancer and noncancer patients who received palliative care. Totally, 226 patients with cancer and 115 noncancer patients received palliative care consultation service in Taiwan from September 2007 through December 2009 were retrospectively analyzed. Noncancer patients were older (81 vs 67 years, P < .001), more likely to be enrolled from an intensive care unit (51% vs 5%, P < .001), and waited longer to be referred for admission to a palliative care (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Emotional disturbance, disease awareness, and accommodation disturbance were reported as the most common manifestations of psychosocial distress among terminal patients with cancer in similar palliative care settings in Taiwan. 14,25 Our study reported a similar pattern and prevalence of psychosocial distress among both patients with hematologic malignancy and patients with solid cancer. In this study, the prevalence of psychosocial distress was not significantly different between the 2 groups, except for a higher prevalence of emotional disturbance among patients with hematologic malignancy than those with solid cancer.…”
Section: Discussionsupporting
confidence: 70%
“…Emotional disturbance, disease awareness, and accommodation disturbance were reported as the most common manifestations of psychosocial distress among terminal patients with cancer in similar palliative care settings in Taiwan. 14,25 Our study reported a similar pattern and prevalence of psychosocial distress among both patients with hematologic malignancy and patients with solid cancer. In this study, the prevalence of psychosocial distress was not significantly different between the 2 groups, except for a higher prevalence of emotional disturbance among patients with hematologic malignancy than those with solid cancer.…”
Section: Discussionsupporting
confidence: 70%
“…It leads to strengthened relationships and improved emotional stability especially concerning confrontation with death [4]. Additionally, IPCC has shown to enhance patients' awareness of the disease including its prognosis [26].…”
Section: Introductionmentioning
confidence: 99%
“…23 A significant increase in DNR designation after PCCS care has been reported in patients with cancers or non-cancer diseases. 5 Our previous study demonstrated that the effect of PCCS on DNR designation mainly resulted from increased patients’/families’ disease awareness and a longer duration of PCCS care. 24 To achieve a better assessment of DNR designation probabilities, medical personnel should refer patients to the PCCS earlier and for longer durations, and promote patients’/families’ awareness of cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Limited hospice resource was one of the major reasons for slow growth in hospice utilization. 35 In addition, patients’ lack of awareness of their diseases and prognoses, 6,7 philosophies of end-of-life and misinterpretations about the functions of hospice units (places for dying) also delayed growth of hospice use.…”
Section: Introductionmentioning
confidence: 99%